“I Have Dutch Nationality, But Others Do Not See Me as a Dutchman, of Course” - Visser-Vogel, Elsbeth (Journal of Muslims in Europe, 2018)
This interview study examines the attitudes of orthoprax young Muslim adults in the Netherlands toward their context, by distinguishing their perceptions of society and their participation in society. In this study, we discover that orthoprax young Muslim adults oppose themselves to Dutch society and do not feel really connected to it. However, most of the time, they participate in society by having jobs, studying and having friends. We also see that respondents are particularly active in and involved with their own Islamic community. Respondents in many cases do not link their religious identity to their participation in society. This study shows three different styles of linking religion to participation: “Participating as far as Islam allows,” “Religion is very personal and individual,” and “Bridging the gap.” We discuss what the reason is for not linking religious identity to participation.